Pengembangan Budidaya Tanaman Sayuran dengan Sistem Hidroponik sebagai Atraksi Wisata di Destinasi Wisata Muara Selayar Desa Pijot - Embun Suryani; Siti Aisyah Hidayati; Sarifudin Sarifudin; Muhamad Akhyar; Lalu M Furkan (Jurnal Gema Ngabdi, 2022)
Pijot Village has very important marine tourism potential, because it is the closest gateway to enter the Pink Beach tourist areas and 27 Gili through the waters. This potential increases with the operation of the Mandalika International Circuit, because Pijot Village as one of the Buffer Villages has an important role to support tourism development on the island of Lombok. One of the tourist areas that can be developed in Pijot Village is the Ar Muara Selayar tourist area. However, the tourism potential of the village is still not well organized, not sustainable, and still partial. Muara Selayar area is a coastal area, where horticultural plants cannot grow properly due to the type of soil and high demand for fresh water. Meanwhile, one of the obstacles in this area is the lack of fresh water supply. For this reason, the development of hydroponics is a solution to these problems. The development of vegetable cultivation with a hydroponic system can have two functions, namely meeting the need for fresh vegetables for the needs of the community and tourist areas and at the same time becoming an attractive tourist attraction. Where tourists can pick the desired vegetables themselves and buy from the community or also meet the needs of culinary processing in this tourist area. This service activity aims to provide training and assistance in the development of vegetable cultivation with a hydroponic system. To achieve this target, a Participatory Rural Appraisal approach is used which emphasizes community involvement in all activities starting from planning, implementing and evaluating programs. This activity is divided into three, namely: 1) socialization on the establishment and management of tourist destinations and attractions; 2) demonstration plot for developing vegetable cultivation with a hydroponic system; and 3) assistance in managing the Muara Selayar Tourism destination in Pijot Village. This activity was carried out in partnership with two target groups, namely Pokdarwis and the Pijot Village PKK Group. The result of this activity is the formation of a PKK group that is able to maintain hydroponic vegetable plants to serve as a food source, as well as make it a tourist attraction. After doing this activity the target group is able to meet their daily vegetable needs continuously.